2016
DOI: 10.1186/s40478-016-0294-7
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of C-terminally truncated Aβ species Aβ37 and Aβ39 in Alzheimer’s disease and transgenic mouse models

Abstract: In Alzheimer’s disease (AD) a variety of amyloid β-peptides (Aβ) are deposited in the form of extracellular diffuse and neuritic plaques (NP), as well as within the vasculature. The generation of Aβ from its precursor, the amyloid precursor protein (APP), is a highly complex procedure that involves subsequent proteolysis of APP by β- and γ-secretases. Brain accumulation of Aβ due to impaired Aβ degradation and/or altered ratios between the different Aβ species produced is believed to play a pivotal role in AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 59 publications
(76 reference statements)
4
28
0
1
Order By: Relevance
“…The tgAPP SWE mouse model appeared to exhibit primarily C-terminally truncated peptides. Here, as previously shown through IHC, Ab1-40, Ab1-39, Ab1-38, and Ab1-37 were observed along with the commonly recognized Ab1-42 (Reinert et al 2016). In agreement with previous observations in tgAPP ArcSwe mice, Ab1-40 was found in our study to be the primary Ab peptide species in the observed Ab plaques (Carlred et al 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The tgAPP SWE mouse model appeared to exhibit primarily C-terminally truncated peptides. Here, as previously shown through IHC, Ab1-40, Ab1-39, Ab1-38, and Ab1-37 were observed along with the commonly recognized Ab1-42 (Reinert et al 2016). In agreement with previous observations in tgAPP ArcSwe mice, Ab1-40 was found in our study to be the primary Ab peptide species in the observed Ab plaques (Carlred et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…In line with these data, plaque pathology-associated deposition of multiple C-terminally truncated peptides (Ab1-37, Ab1-38, Ab1-39 and Ab1-40) was previously described for familial AD (FAD) cases with the Swedish APP mutation (Reinert et al 2014;Reinert et al 2016) as well as in various transgenic mouse models carrying this mutation (Hsiao et al 1996;Kawarabayashi et al 2001;Kuo et al 2001;Reinert et al 2016).…”
Section: Discussionsupporting
confidence: 63%
“…To validate the relevance of ADAMTS4 for Aβ generation and APP processing in vivo, ADAMTS4 −/− knockout (KO) mice were crossed to the 5xFAD model of AD [54,61]. Consistent with previous results [62], mass spectrometry analysis of Aβ peptide species in the brains of 12-month-old Supplementary Fig. S4).…”
Section: Genetic Deletion Of Adamts4 Lowers Aβ4-x and Increases Apps mentioning
confidence: 77%
“…From these, M139V (TM2), M146L (TM2), L166P (TM2), and G384A (TM7) mutations have been associated with an increase in Aβ42 production, due to conformational alterations in PS1 and PS1‐APP complex interactions ,. These changes in the PS1 conformation have also been observed in the TM6–TM7 loop with both exon 9 deletion (E9Δ, T291_S319del) and L286V mutation ,. Moreover, a previous study demonstrated that the PS1 protein with E9Δ is not subject to endoproteolytic processing, since this lacks the cleavage site .…”
Section: Factors That Regulate γ‐Secretase Activitymentioning
confidence: 90%